Menguak Sejarah Tsunami Maumere Tahun 1992 Di Wuring - Dalopes, Fransisco Alfredo Resude; Ande, Andreas; Utomo, Susilo Setyo (Universitas Nusa Cendana, 2024)
The purpose of this study is to determine the history of the 1992 Maumere tsunami in Wuring Village and to understand life before and after the 1992 Maumere tsunami in Wuring Village. The results of the study show that: 1. The tsunami that occurred on December 12, 1992, struck the central and eastern parts of Flores Island. In addition to destroying infrastructure, the tsunami also claimed thousands of lives. As a result of this natural disaster, the community was gripped by fear, trauma, and worry. 2. After the tsunami disaster, there were changes in people's lives, from their places of residence to their livelihoods. Therefore, the government needs to conduct socialization in the community about disaster preparedness, and the community must be more caring, aware, and capable of being prepared to face disasters.